The elementary education Turkish Republic Revolution History and Kemalism course curriculum from the perspectives of social sciences faculty members - Kaya Yılmaz; Yakup Ayaydın (Turkish History Education Journal)
This study was conducted to investigate the perspectives of social sciences faculty members on the development of the Turkish Republic History of Revolution and Kemalism Curriculum for eighth-grade education in Turkey. The study was carried out via the Qualitative Research Method. The study participants consisted of 15 faculty members from eight different universities in Turkey. The Purposive Sampling Method was used in the selection process of the research participants. A semi-structured interview protocol developed by the researcher based on expert opinions was used to collect research data. The Descriptive Analysis Method was employed to analyse the obtained data. The study results showed that according to the faculty members, the curriculum under scrutiny should be developed through a learner-centred approach, the name of the curriculum should be changed, the time allocated for the units should be adjusted, the content of the curriculum should form a link between the past and the present, and the curriculum should make more emphasis on the economic, social and cultural developments by incorporating different perspectives. The faculty members stated that the course objectives should be developed by taking the nation’s recent past into account, emphasizing a sense of unity and solidarity, homeland-nation consciousness, and the struggles of the Turkish Republic in gaining its independence. The faculty members suggested that the learning outcomes of the curriculum should be simplified by reducing the number of standards, ensuring the balance between the time allocated for teaching and learning outcomes. From the perspectives of the participants, the curriculum should be redesigned under the principles of the Constructivist Learning Theory or learner-centred education so that students can gain a deep understanding of the subject and develop their higher-level thinking skills.